High Sucrose Diet-Induced Subunit I Tyrosine 304 Phosphorylation of Cytochrome c Oxidase Leads to Liver Mitochondrial Respiratory Dysfunction in the Cohen Diabetic Rat Model - Tasnim Arroum; Lucynda Pham; Taryn E. Raisanen; Paul T. Morse; Junmei Wan; Jamie Bell; Rachel Lax; Ann Saada; Maik Hüttemann; Sarah Weksler-Zangen (Antioxidants, 2023)
The mitochondrial oxidative phosphorylation process generates most of the cellular energy and free radicals in mammalian tissues. Both factors play a critical role in numerous human diseases that could be affected by reversible phosphorylation events that regulate the function and activity of the oxidative phosphorylation complexes. In this study, we analyzed liver mitochondria of Cohen diabetes-sensitive (CDs) and Cohen diabetes-resistant (CDr) rats, using blue native gel electrophoresis (BN-PAGE) in combination with mitochondrial activity measurements and a site-specific tyrosine phosphorylation implicated in inflammation, a known driver of diabetes pathology. We uncovered the presence of a specific inhibitory phosphorylation on tyrosine 304 of catalytic subunit I of dimeric cytochrome c oxidase (CcO, complex IV). Driven by a high sucrose diet in both CDr and CDs rats, Y304 phosphorylation, which occurs close to the catalytic oxygen binding site, correlates with a decrease in CcO activity and respiratory dysfunction in rat liver tissue under hyperglycemic conditions. We propose that this phosphorylation, specifically seen in dimeric CcO and induced by high sucrose diet-mediated inflammatory signaling, triggers enzymatic activity decline of complex IV dimers and the assembly of supercomplexes in liver tissue as a molecular mechanism underlying a (pre-)diabetic phenotype.